2017
DOI: 10.1007/978-3-319-55858-5_13
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial VDAC, the Na+/Ca2+ Exchanger, and the Ca2+ Uniporter in Ca2+ Dynamics and Signaling

Abstract: Mitochondrial Ca uptake and release play pivotal roles in cellular physiology by regulating intracellular Ca signaling, energy metabolism, and cell death. Ca transport across the inner and outer mitochondrial membranes (IMM, OMM, respectively), is mediated by several proteins, including the voltage-dependent anion channel 1 (VDAC1) in the OMM, and the mitochondrial Ca uniporter (MCU) and Na-dependent mitochondrial Ca efflux transporter, (the NCLX), both in the IMM. By transporting Ca across the OMM to the mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 184 publications
0
20
0
Order By: Relevance
“…Together, these data are consistent with excess TSPO being a negative modulator of mitochondrial Ca 2+ entry, potentially by interacting with and modulating VDAC open probability 21 . VDAC operates at the OMM, and controls Ca 2+ entry into the intermembrane space in series with the mitochondrial Ca 2+ uniporter (MCU) on the IMM 46 , 47 . A recent study 13 demonstrated that reducing Ca 2+ flux via VDAC severely affected heart contractility in zebra fish, while interventions to increase Ca 2+ flux through the OMM restored normal contraction of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data are consistent with excess TSPO being a negative modulator of mitochondrial Ca 2+ entry, potentially by interacting with and modulating VDAC open probability 21 . VDAC operates at the OMM, and controls Ca 2+ entry into the intermembrane space in series with the mitochondrial Ca 2+ uniporter (MCU) on the IMM 46 , 47 . A recent study 13 demonstrated that reducing Ca 2+ flux via VDAC severely affected heart contractility in zebra fish, while interventions to increase Ca 2+ flux through the OMM restored normal contraction of the heart.…”
Section: Discussionmentioning
confidence: 99%
“…The voltage-dependent anion channel type 1 (VDAC1) protein located in the outer mitochondrial membrane regulates mitochondrial import and export of ions and metabolites, including Ca 2+ , ATP and NADH, and thereby regulates oxidative phosphorylation (18). VDAC1 is also involved in regulating cell death through interactions with various proteins including hexokinase (HK), Bcl-2 and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (19).…”
Section: Introductionmentioning
confidence: 99%
“…Many proteins are translocated to the mitochondria or other organelles by the Hsp70 system under certain growth conditions [ 12 , 13 , 14 ]. Since the frequently used technique of culturing fungi on glass slides for microscopic studies may lead to false conclusions, results need to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mitochondrial import pathways leads through Porin, an oligomeric protein located in the mitochondrial outer membrane. Porin1, also known as the voltage-dependent anion channel (VDAC-1), participates in the mitochondrial import of multiple proteins and other low-molecular-weight compounds [ 12 , 13 ]. In humans, the Hsp90 chaperone was shown to primarily facilitate the import of proteins into the Porin1 channel with less Hsp70 involvement, whereas in fungi, Hsp70 is mostly responsible for this import [ 14 ].…”
Section: Introductionmentioning
confidence: 99%